The book of webs - Kohn, Jesse (Juniper prize for fiction, 2023)
"Word spreads from one recovering self-inflicted eye surgery patient to the next of a mystical book capable of overturning the Burlingtonian empire. Captivating and devious, the book of webs is constructed out of misremembered fragments, conflicting histories, and secrets whispered in the darkness. The insurgents tell of an enemy so powerful it owns the air, dictates reality, and has even managed to co-opt their thoughts. Their only hope is to conspire with the uprisings of their bodies: slips of the tongue, excretions, tics, bad hair days, and, most importantly, their dreams. In this darkly comic and inventive debut novel, Jesse Kohn introduces a network of shape-shifters and misfits. A militant priestess broods over orphaned angel eggs. A post-punk band animates a messianic homunculus made of belly button lint. A failed dream journalist goes on a terrible first date to heaven. Each misadventure is a chapter in a book devised to oppose the despotic order of their enemy-the book of webs"--